Internet of Thing untuk Memantau Sistem Kelistrikkan Pembudidaya Ikan Hias - Dwiyaniti, Murie; Riandini, Riandini; Silawardono, Silawardono; Tahazen, Tahazen; Saputra, Fauzan Aziz; Yosmaniar, Yosmaniar (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
The Pondakan Alam Sari ornamental fish cultivator group has approximately 50 types of ornamental fish cultivated for domestic and foreign commodities. Market demand for ornamental fish tends to increase yearly, but the market wants stable prices. This price stability is a dilemma for ornamental fish cultivator groups. One of the determinants of the selling price of ornamental fish is operational costs, especially electricity costs. The increase in basic electricity tariffs causes operational costs to increase. Electricity is used to power the circulating water pump 24 hours non-stop daily. This circulating water pump is very important for producing oxygen in the water. If there is no oxygen in the water, ornamental fish will die. To reduce operational electricity costs, the community service team built a DC electricity system sourced from solar energy so that the circulating water pump source no longer uses PLN electricity. This community service program aims to reduce operational electricity costs by building a DC electricity system sourced from solar energy and an IoT-based monitoring process. The implementation method consists of two stages: (1) building physical capital through a solar energy electricity source and DC pump installation and (2) creating a DC electrical parameter monitoring system with the Blynk IoT platform. The evaluation technique was carried out by comparing planning with the progress of implementing activities. The results and implications of activities include the availability of DC electricity sources from renewable energy, namely solar cells with a power of 960 WP, installing 10 DC pumps, and an IoT-based DC electrical parameter monitoring system. Operational costs in managing an ornamental fish business can be reduced by 46% from before using renewable and IoT-based energy. This result will certainly increase the profit margin of ornamental fish farming.